Red Palm Mite, Raoiella indica Hirst (Arachnida: Acari: Tenuipalpidae) - Marjorie A. Hoy; Jorge Peña; Ru Nguyen (EDIS)
EENY-397, a 6-page illustrated fact sheet by Marjorie A. Hoy, Jorge Peña and Ru Nguyen, describes this pest of several important ornamental and fruit-bearing palm species that is in the process of colonizing islands in the Carribean.  Includes sections on distribution; description and life cycle; hosts; survey, detection and damage; management; and selected references.  Published by the UF Department of Entomology and Nematology, November 2006. Revised April 2010.